Acceptance Tests of more than 10 000 Photomultiplier Tubes for the multi-PMT Digital Optical Modules of the IceCube Upgrade - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
More than 10 000 photomultiplier tubes (PMTs) with a diameter of 80 mm will be installed in multi-PMT Digital Optical Modules (mDOMs) of the IceCube Upgrade. These have been tested and pre-calibrated at two sites. A throughput of more than 1000 PMTs per week with both sites was achieved with a modular design of the testing facilities and highly automated testing procedures. The testing facilities can easily be adapted to other PMTs, such that they can, e.g., be re-used for testing the PMTs for IceCube-Gen2. Single photoelectron response, high voltage dependence, time resolution, prepulse, late pulse, afterpulse probabilities, and dark rates were measured for each PMT. We describe the design of the testing facilities, the testing procedures, and the results of the acceptance tests.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cherenkov detectors; Neutrino detectors; Photon detectors for UV; HPDs; others); visible and IR photons (vacuum) (photomultipliers

Accounting for changing snow over 10 years of IceTop, and its impact on the all-particle cosmic ray spectrum - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceTop surface detector of the IceCube Neutrino Observatory measures extensive air showers (EAS). Coincident signals in both tanks of an IceTop station result primarily from the electromagnetic component of the EAS, and events which trigger at least 5 stations correspond to energies roughly above the knee, with an energy threshold and reconstruction behavior that changes over time as snow accumulates above the array. We present a status report of an analysis of ≥ 5-station events in IceTop from 2011-2021, which will be used to measure the all-particle spectrum of cosmic rays in the transition region from galactic to extragalactic sources up to EeV range, using updated simulations and improved treatments of snow attenuation. In particular, a snow model has been developed which takes the non-attenuating muon content of tank signals, as well as their saturation behavior, into account.
CRIS-Team Scopus Importer:2025-02-04

A Hierarchical Bayesian Approach to Point-source Analysis in High-energy Neutrino Telescopes - Capel, Francesca; Kuhlmann, Julian; Haack, Christian; Ha Minh, Martin; Niederhausen, Hans; Schumacher, Lisa (Astrophysical Journal, 2024)
We propose a novel approach to the detection of point-like sources of high-energy neutrinos. Motivated by evidence for emerging sources in existing data, we focus on the characterization and interpretation of these sources rather than the rejection of the background-only hypothesis. The hierarchical Bayesian model is implemented in the Stan platform, enabling computation of the posterior distribution with a Hamiltonian Monte Carlo algorithm. We simulate a population of weak neutrino sources detected by the IceCube experiment and use the resulting data set to demonstrate and validate our framework. We show that even for the challenging case of sources at the threshold of detection and using limited prior information, it is possible to correctly infer the source properties. Additionally, we demonstrate how modeling flexible connections between similar sources can be used to recover the contribution of sources that would not be detectable individually. While a direct comparison of our method to existing approaches is challenged by the fundamental differences in frequentist and Bayesian frameworks, we draw parallels where possible. In particular, we highlight how including more complexity into the source modeling can increase the sensitivity to sources and their populations.
CRIS-Team Scopus Importer:2024-11-29

An improved infrastructure for the IceCube realtime system - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube realtime alert system has been operating since 2016. It provides prompt alerts on high-energy neutrino events to the astroparticle physics community. The localization regions for the incoming direction of neutrinos are published through NASA’s Gamma-ray Coordinate Network (GCN). The IceCube realtime system consists of infrastructure dedicated to the selection of alert events, the reconstruction of their topology and arrival direction, the calculation of directional uncertainty contours and the distribution of the event information through public alert networks. Using a message-based workflow management system, a dedicated software (SkyDriver) provides a representational state transfer (REST) interface to parallelized reconstruction algorithms. In this contribution, we outline the improvements of the internal infrastructure of the IceCube realtime system that aims to streamline the internal handling of neutrino events, their distribution to the SkyDriver interface, the collection of the reconstruction results as well as their conversion into human- and machine-readable alerts to be publicly distributed through different alert networks. An approach for the long-term storage and cataloging of alert events according to findability, accessibility, interoperability and reusability (FAIR) principles is outlined.
CRIS-Team Scopus Importer:2025-02-04

Beyond the null hypothesis: Physics-driven searches for astrophysical neutrino sources - Capel, Francesca; Kuhlmann, Julian; Haack, Christian; Minh, Martin Ha; Niederhausen, Hans; Schumacher, Lisa (Proceedings of Science, 2024)
While there have been multiple reports of potential links between astrophysical sources and high-energy neutrinos, definitively identifying these sources remains challenging. No single result has surpassed the significance threshold for discovery, and the theoretical interpretation of these observations has revealed new questions for the bigger picture of neutrino astrophysics. In response to these difficulties, we propose a novel approach that combines state-of-the-art methods with the wealth of information from multi-messenger observations and theoretical models. Our physics-first strategy utilizes advanced techniques such as Hamiltonian Monte Carlo and hierarchical modelling to navigate the high-dimensional space of parameters and uncertainties in this complex setting. Implementing these methods within a Bayesian framework offers a unique perspective on source discovery while enabling us to avoid pitfalls associated with trial factors. Furthermore, considering source populations provides additional constraints from observations and uncovers further implications from a broader perspective, making the most of the existing high-energy neutrino data. We demonstrate the impact of these methods through application to simulated data, considering relevant multi-messenger scenarios for sources and their populations. Our approach complements existing techniques while offering increased sensitivity and interpretability in the context of investigating specific physical models, potentially accelerating decisive discoveries.
CRIS-Team Scopus Importer:2025-02-04

Characterization of the astrophysical diffuse neutrino flux using starting track events in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2024)
A measurement of the diffuse astrophysical neutrino spectrum is presented using IceCube data collected from 2011-2022 (10.3 years). We developed novel detection techniques to search for events with a contained vertex and exiting track induced by muon neutrinos undergoing a charged-current interaction. Searching for these starting track events allows us to not only more effectively reject atmospheric muons but also atmospheric neutrino backgrounds in the southern sky, opening a new window to the sub-100 TeV astrophysical neutrino sky. The event selection is constructed using a dynamic starting track veto and machine learning algorithms. We use this data to measure the astrophysical diffuse flux as a single power law flux (SPL) with a best-fit spectral index of γ=2.58-0.09+0.10 and per-flavor normalization of φper-flavorAstro=1.68-0.22+0.19×10-18×GeV-1 cm-2 s-1 sr-1 (at 100 TeV). The sensitive energy range for this dataset is 3-550 TeV under the SPL assumption. This data was also used to measure the flux under a broken power law, however we did not find any evidence of a low energy cutoff.
CRIS-Team Scopus Importer:2024-07-19

Citizen science for IceCube: Name that Neutrino - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (European Physical Journal Plus, 2024)
Name that Neutrino is a citizen science project where volunteers aid in classification of events for the IceCube Neutrino Observatory, an immense particle detector at the geographic South Pole. From March 2023 to September 2023, volunteers did classifications of videos produced from simulated data of both neutrino signal and background interactions. Name that Neutrino obtained more than 128,000 classifications by over 1800 registered volunteers that were compared to results obtained by a deep neural network machine-learning algorithm. Possible improvements for both Name that Neutrino and the deep neural network are discussed.
CRIS-Team Scopus Importer:2024-06-28

Data-based evaluation of direction reconstruction for IceCube cascade events by utilizing starting tracks - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube Neutrino Observatory instruments a cubic-kilometer of glacial ice and has been the first experiment to identify high-energy astrophysical neutrinos. There are two main morphologies of IceCube events: tracks and cascades. Tracks result from muons, while cascades result from particle showers induced by in-ice interactions. The directional reconstruction of cascades is less precise than that of tracks, which limits the sensitivity of astrophysical neutrino analyses with cascade events. In order to improve the directional reconstruction of cascade events, accurate ice modeling is essential. However, potential biases might exist in data stemming from unconstrained systematic uncertainties. In this work, feasibility studies to better understand the ice using a data-driven approach are performed, where photons that are likely to have been induced by the hadronic cascade part of muon neutrino charged-current interactions are categorized using probability density functions in time, distance and angle, and the reconstructed direction with this pseudo-cascade is compared with the track direction. In this proceedings, methodology and results are detailed and a path towards better understanding of the ice is discussed.
CRIS-Team Scopus Importer:2025-02-04

Estimating the coincidence rate between the optical and radio array of IceCube-Gen2 - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube-Gen2 Neutrino Observatory is proposed to extend the all-flavour energy range of IceCube beyond PeV energies. It will comprise two key components: I) An enlarged 8 km3 in-ice optical Cherenkov array to measure the continuation of the IceCube astrophysical neutrino flux and improve IceCube’s point source sensitivity above ∼ 100 TeV; and II) A very large in-ice radio array with a surface area of about 500 km2. Radio waves propagate through ice with a kilometer-long attenuation length, hence a sparse radio array allows us to instrument a huge volume of ice to achieve a sufficient sensitivity to detect neutrinos with energies above tens of PeV. The different signal topologies for neutrino-induced events measured by the optical and in-ice radio detector - the radio detector is mostly sensitive to the cascades produced in the neutrino interaction, while the optical detector can detect long-ranging muon and tau leptons with high accuracy - yield highly complementary information. When detected in coincidence, these signals will allow us to reconstruct the neutrino energy and arrival direction with high fidelity. Furthermore, if events are detected in coincidence with a sufficient rate, they resemble the unique opportunity to study systematic uncertainties and to cross-calibrate both detector components. We present the expected rate of coincidence events for 10 years of operation. Furthermore, we analyzed possible detector optimizations to increase the coincidence rate.
CRIS-Team Scopus Importer:2025-02-04

Evaluation of an FPGA-based fast machine-learning trigger for neutrino telescopes - Capel, Francesca; Spannfellner, Christian; Haack, Christian; Prottung, Janik (Proceedings of Science, 2024)
Energetic neutrinos provide a view into the underlying processes of astrophysical particle accelerators, but their weakly interacting nature makes them challenging to detect. Current experiments instrument large volumes of ice or water with 3D grids of photomultiplier tubes (PMTs) to capture the Cherenkov light produced by interactions of high-energy neutrinos. Such detectors must be located in remote locations deep underwater or in ice to reduce atmospheric background signals. These challenging conditions impose strict limits on the power and bandwidth available for data transfer to the surface, and triggers are used to maintain manageable rates. We evaluate the potential of fast, intelligent machine-learning triggers that can be implemented on low-power field-programmable gate arrays (FPGAs). We aim to make the most of the given hardware with improved discrimination of signal and background and therefore improved sensitivity to low-energy events. In particular, we focus on the case of underwater neutrino detectors and the efficient discrimination of track-like signals from the bioluminescence background. We develop a machine-learning trigger by using the planned P-ONE experiment as a case study and implement a software testbench to compare its performance to a less complex trigger design based on coincident detections.
CRIS-Team Scopus Importer:2025-02-04

Exploration of mass splitting and muon/tau mixing parameters for an eV-scale sterile neutrino with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physics Letters B, 2024)
We present the first three-parameter fit to a 3+1 sterile neutrino model using 7.634 years of data from the IceCube Neutrino Observatory on νμ+ν‾μ charged-current interactions in the energy range 500–9976 GeV. Our analysis is sensitive to the mass-squared splitting between the heaviest and lightest mass state (Δm412), the mixing matrix element connecting muon flavor to the fourth mass state (|Uμ4|2), and the element connecting tau flavor to the fourth mass state (|Uτ4|2). Predicted propagation effects in matter enhance the signature through a resonance as atmospheric neutrinos from the Northern Hemisphere traverse the Earth to the IceCube detector at the South Pole. The remaining sterile neutrino matrix elements are left fixed, with |Ue4|2=0 and δ14=0, as they have a negligible effect, and δ24=π is set to give the most conservative limits. The result is consistent with the no-sterile neutrino hypothesis with a probability of 4.3%. Profiling the likelihood of each parameter yields the 90% confidence levels: 2.4eV2<Δm412<9.6eV2, 0.0081<|Uμ4|2<0.10, and |Uτ4|2<0.035, which narrows the allowed parameter-space for |Uτ4|2. However, the primary result of this analysis is the first map of the 3+1 parameter space exploring the interdependence of Δm412, |Uμ4|2, and |Uτ4|2.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Atmospheric neutrino IceCube TeV oscillation sterile

Improved modeling of in-ice particle showers for IceCube event reconstruction - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
The IceCube Neutrino Observatory relies on an array of photomultiplier tubes to detect Cherenkov light produced by charged particles in the South Pole ice. IceCube data analyses depend on an in-depth characterization of the glacial ice, and on novel approaches in event reconstruction that utilize fast approximations of photoelectron yields. Here, a more accurate model is derived for event reconstruction that better captures our current knowledge of ice optical properties. When evaluated on a Monte Carlo simulation set, the median angular resolution for in-ice particle showers improves by over a factor of three compared to a reconstruction based on a simplified model of the ice. The most substantial improvement is obtained when including effects of birefringence due to the polycrystalline structure of the ice. When evaluated on data classified as particle showers in the high-energy starting events sample, a significantly improved description of the events is observed.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Cherenkov detectors; Neutrino detectors; programs; Simulation methods

Methods and stability tests associated with the sterile neutrino search using improved high-energy νμ event reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We provide supporting details for the search for a 3+1 sterile neutrino using data collected over 10.7 years at the IceCube Neutrino Observatory. The analysis uses atmospheric muon-flavored neutrinos from 0.5 to 100 TeV that traverse Earth to reach the IceCube detector and finds a best-fit point at sin2(2θ24)=0.16 and Δm412=3.5 eV2 with a goodness-of-fit p value of 12% and consistency with the null hypothesis of no oscillations to sterile neutrinos with a p value of 3.1%. Several improvements were made over past analyses, which are reviewed in this article, including upgrades to the reconstruction and the study of sources of systematic uncertainty. We provide details of the fit quality and discuss stability tests that split the data for separate samples, comparing results. We find that the fits are consistent between split datasets.
CRIS-Team Scopus Importer:2024-11-29

Multi-flavour neutrino searches from the Milky Way Galaxy - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
High-energy neutrinos are expected to be produced in the Milky Way by cosmic ray interactions at sites of acceleration or during their propagation. Neutrinos provide distinctive information on hadronic interactions and can be pointed back to production origins, unraveling unique properties of the Galaxy. We present an analysis on the search for the diffuse neutrino flux along the Galactic Plane by using data collected at the largest operating neutrino telescope in the world - the IceCube Neutrino Observatory. More than 10 years of data since the completion of the detector are used in this analysis. We utilize three event selections including through-going tracks, showers and starting-tracks to reach full-sky coverage and to be sensitive to all three neutrino flavours.
CRIS-Team Scopus Importer:2025-02-04

Observation of high-energy neutrinos from the Galactic plane - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceCube has discovered a flux of astrophysical neutrinos and presented evidence for the first neutrino sources, a flaring blazar known as TXS 0506+056 and the active galaxy NGC 1068. However, the sources responsible for the majority of the astrophysical neutrino flux remain elusive. In addition to hypothetical sources within our Galaxy, high energy neutrinos are produced when cosmic rays interact at their acceleration sites and during propagation through the interstellar medium. The Galactic plane has therefore long been hypothesized as a neutrino source. In this contribution, new results are presented for searches of neutrino sources utilizing a dataset that builds upon recent advances in deep-learning-based reconstruction methods for neutrino-induced cascades. This work presents the first observation of high-energy neutrinos from the Milky Way Galaxy, rejecting the background-only hypothesis at 4.5 σ. The neutrino signal is consistent with diffuse emission from the Galactic plane, potentially in combination with emission by a population of sources.
CRIS-Team Scopus Importer:2025-02-04

Observation of Seven Astrophysical Tau Neutrino Candidates with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review Letters, 2024)
We report on a measurement of astrophysical tau neutrinos with 9.7 yr of IceCube data. Using convolutional neural networks trained on images derived from simulated events, seven candidate ντ events were found with visible energies ranging from roughly 20 TeV to 1 PeV and a median expected parent ντ energy of about 200 TeV. Considering backgrounds from astrophysical and atmospheric neutrinos, and muons from π±/K± decays in atmospheric air showers, we obtain a total estimated background of about 0.5 events, dominated by non-ντ astrophysical neutrinos. Thus, we rule out the absence of astrophysical ντ at the 5σ level. The measured astrophysical ντ flux is consistent with expectations based on previously published IceCube astrophysical neutrino flux measurements and neutrino oscillations.
CRIS-Team Scopus Importer:2024-04-26

Probing the Connection between IceCube Neutrinos and MOJAVE AGN - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Astrophysical Journal, 2024)
Active galactic nuclei (AGN) are prime candidate sources of the high-energy, astrophysical neutrinos detected by IceCube. This is demonstrated by the real-time multimessenger detection of the blazar TXS 0506+056 and the recent evidence of neutrino emission from NGC 1068 from a separate time-averaged study. However, the production mechanism of the astrophysical neutrinos in AGN is not well established, which can be resolved via correlation studies with photon observations. For neutrinos produced due to photohadronic interactions in AGN, in addition to a correlation of neutrinos with high-energy photons, there would also be a correlation of neutrinos with photons emitted at radio wavelengths. In this work, we perform an in-depth stacking study of the correlation between 15 GHz radio observations of AGN reported in the MOJAVE XV catalog, and 10 yr of neutrino data from IceCube. We also use a time-dependent approach, which improves the statistical power of the stacking analysis. No significant correlation was found for both analyses, and upper limits are reported. When compared to the IceCube diffuse flux, at 100 TeV and for a spectral index of 2.5, the upper limits derived are ∼3% and ∼9% for the time-averaged and time-dependent cases, respectively.
CRIS-Team Scopus Importer:2024-10-11

Search for a light sterile neutrino with 7.5 years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We present a search for an eV-scale sterile neutrino using 7.5 years of data from the IceCube DeepCore detector. The analysis uses a sample of 21,914 events with energies between 5 and 150 GeV to search for sterile neutrinos through atmospheric muon neutrino disappearance. Improvements in event selection and treatment of systematic uncertainties provide greater statistical power compared to previous DeepCore sterile neutrino searches. Our results are compatible with the absence of mixing between active and sterile neutrino states, and we place constraints on the mixing matrix elements |Uμ4|2<0.0534 and |Uτ4|2<0.0574 at 90% CL under the assumption that Δm412≥1 eV2. These null results add to the growing tension between anomalous appearance results and constraints from disappearance searches in the 3+1 sterile neutrino landscape.
CRIS-Team Scopus Importer:2024-11-01

Search for an eV-Scale Sterile Neutrino Using Improved High-Energy νμ Event Reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review Letters, 2024)
This Letter presents the result of a 3+1 sterile neutrino search using 10.7 yr of IceCube data. We analyze atmospheric muon neutrinos that traverse the Earth with energies ranging from 0.5 to 100 TeV, incorporating significant improvements in modeling neutrino flux and detector response compared to earlier studies. Notably, for the first time, we categorize data into starting and throughgoing events, distinguishing neutrino interactions with vertices inside or outside the instrumented volume, to improve energy resolution. The best-fit point for a 3+1 model is found to be at sin2(2θ24)=0.16 and Δm412=3.5 eV2, which agrees with previous iterations of this Letter. The result is consistent with the null hypothesis of no sterile neutrinos with a p value of 3.1%.
CRIS-Team Scopus Importer:2024-12-06

Search for decoherence from quantum gravity with atmospheric neutrinos - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Nature Physics, 2024)
Neutrino oscillations at the highest energies and longest baselines can be used to study the structure of spacetime and test the fundamental principles of quantum mechanics. If the metric of spacetime has a quantum mechanical description, its fluctuations at the Planck scale are expected to introduce non-unitary effects that are inconsistent with the standard unitary time evolution of quantum mechanics. Neutrinos interacting with such fluctuations would lose their quantum coherence, deviating from the expected oscillatory flavour composition at long distances and high energies. Here we use atmospheric neutrinos detected by the IceCube South Pole Neutrino Observatory in the energy range of 0.5–10.0 TeV to search for coherence loss in neutrino propagation. We find no evidence of anomalous neutrino decoherence and determine limits on neutrino–quantum gravity interactions. The constraint on the effective decoherence strength parameter within an energy-independent decoherence model improves on previous limits by a factor of 30. For decoherence effects scaling as E2, our limits are advanced by more than six orders of magnitude beyond past measurements compared with the state of the art.
CRIS-Team Scopus Importer:2024-06-14

Search for Galactic Core-collapse Supernovae in a Decade of Data Taken with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2024)
The IceCube Neutrino Observatory has been continuously taking data to search for O(0.5–10) s long neutrino bursts since 2007. Even if a Galactic core-collapse supernova is optically obscured or collapses to a black hole instead of exploding, it will be detectable via the O(10) MeV neutrino burst emitted during the collapse. We discuss a search for such events covering the time between 2008 April 17 and 2019 December 31. Considering the average data taking and analysis uptime of 91.7% after all selection cuts, this is equivalent to 10.735 yr of continuous data taking. In order to test the most conservative neutrino production scenario, the selection cuts were optimized for a model based on an 8.8 solar mass progenitor collapsing to an O–Ne–Mg core. Conservative assumptions on the effects of neutrino oscillations in the exploding star were made. The final selection cut was set to ensure that the probability to detect such a supernova within the Milky Way exceeds 99%. No such neutrino burst was found in the data after performing a blind analysis. Hence, a 90% C.L. upper limit on the rate of core-collapse supernovae out to distances of ≈25 kpc was determined to be 0.23 yr−1. For the more distant Magellanic Clouds, only high neutrino luminosity supernovae will be detectable by IceCube, unless external information on the burst time is available. We determined a model-independent limit by parameterizing the dependence on the neutrino luminosity and the energy spectrum.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Core-collapse supernovae (304); Neutrino telescopes (1105); Supernova neutrinos (1666)

Search for Joint Multimessenger Signals from Potential Galactic Cosmic-Ray Accelerators with HAWC and IceCube - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; et al. (Astrophysical Journal, 2024)
The origin of high-energy galactic cosmic rays is yet to be understood, but some galactic cosmic-ray accelerators can accelerate cosmic rays up to PeV energies. The high-energy cosmic rays are expected to interact with the surrounding material or radiation, resulting in the production of gamma-rays and neutrinos. To optimize for the detection of such associated production of gamma-rays and neutrinos for a given source morphology and spectrum, a multimessenger analysis that combines gamma-rays and neutrinos is required. In this study, we use the MultiMission Maximum Likelihood framework with IceCube Maximum Likelihood Analysis software and HAWC Accelerated Likelihood to search for a correlation between 22 known gamma-ray sources from the third HAWC gamma-ray catalog and 14 yr of IceCube track-like data. No significant neutrino emission from the direction of the HAWC sources was found. We report the best-fit gamma-ray model and 90% CL neutrino flux limit from the 22 sources. From the neutrino flux limit, we conclude that, for five of the sources, the gamma-ray emission observed by HAWC cannot be produced purely from hadronic interactions. We report the limit for the fraction of gammarays produced by hadronic interactions for these five sources.
CRIS-Team Scopus Importer:2024-11-29

Search for the Prompt Atmospheric Neutrino Flux in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
For about a decade the IceCube Neutrino Observatory has been observing a high-energy diffuse astrophysical neutrino flux. At these energies, an important source of background are the prompt atmospheric neutrinos produced in decays of charmed mesons that are part of cosmic-ray-induced air showers. The production yield of charmed mesons in the very forward phase space of hadronic interactions, and thus the flux of prompt neutrinos, is not well known and has not yet been observed by IceCube. A measurement of the flux of prompt neutrinos will improve the modeling of hadronic interactions in cosmic-ray induced air showers at high energies. Additionally, in the context of astrophysical neutrino measurements, understanding this background flux will improve the measurement precision of the spectral shape in the future. In particular, the analysis of up-going muon neutrino-induced tracks in IceCube provides a large sample of atmospheric neutrinos which likely includes prompt neutrinos. However, the measurement of a subdominant prompt neutrino flux strongly depends on the hypothesis for the dominant astrophysical neutrino flux. This makes the estimation of upper limits on the prompt neutrino flux challenging. We discuss the extent of this model dependency on the astrophysical flux and propose a method to calculate robust upper limits. Furthermore, a possible dedicated search of the prompt neutrino flux using multiple IceCube detection channels is outlined.
CRIS-Team Scopus Importer:2025-02-04

The Wavelength-Shifting Optical Module in Application to the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The Wavelength-shifting Optical Module (WOM) is a novel photosensor concept developed as part of the upcoming Upgrade for the IceCube Neutrino Observatory. It uses the technique of wavelength shifting and total internal reflection to increase the photon light yield in the UV-regime of the Cherenkov spectrum. The decoupling of the effective area from the size of light sensors enhances the signal-to-noise-ratio. Twelve WOM modules will be deployed in the IceCube Upgrade to increase the photon detection efficiency and thus enhance future low-energy analyses. The general concept can also be applied at the future IceCube-Gen2 detector, where passive light collecting extensions to the optical sensor modules locally increase the light collection efficiency. This technique would benefit the detection of supernova neutrinos or other particles with low light emissions. We report on new results in characterizing and optimizing the WOM concept, the production status of the modules to be deployed in 2025/26 as well as possible applications of the concept for IceCube-Gen2.
CRIS-Team Scopus Importer:2025-02-04

Three-year performance of the IceAct telescopes at the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceAct is an array of compact Imaging Air Cherenkov Telescopes at the ice surface as part of the IceCube Neutrino Observatory. The telescopes, featuring a camera of 61 silicon photomultipliers and fresnel-lens-based optics, are optimized to be operated in harsh environmental conditions, such as at the South Pole. Since 2019, the first two telescopes have been operating in a stereoscopic configuration in the center of IceCube’s surface detector IceTop. With an energy threshold of about 10 TeV and a wide field-of-view, the IceAct telescopes show promising capabilities of improving current cosmic-ray composition studies: measuring the Cherenkov light emissions in the atmosphere adds new information about the shower development not accessible with the current detectors. First simulations indicate that the added information of a single telescope leads, e.g., to an improved discrimination between flux contributions from different primary particle species in the sensitive energy range. We review the performance and detector operations of the telescopes during the past 3 years (2020-2022) and give an outlook on the future of IceAct.
CRIS-Team Scopus Importer:2025-02-04